Protective immunity induced by DNA vaccine containing TgGRA35, TgGRA42, and TgGRA43 against Toxoplasma gondii infection in Kunming mice - Shi, Youbo; Li, Jianbing; Yang, Weili; Chen, Jia (Frontiers in Cellular and Infection Microbiology, 2023)
Background: Toxoplasma gondii can cause congenital infection and abortion in humans and warm-blooded animals. T. gondii dense granule proteins, GRA35, GRA42, and GRA43 play a critical role in the establishment of chronic infection. However, their potential to induce protective immunity against T. gondii infection remains unexplored. Objective: This study aimed to test the efficacy of DNA vaccine encompassing GRA35, GRA42, and GRA43 in inducing protective immunity against the highly virulent T. gondii RH strain (Type I) and the brain cyst-forming PRU strain (Type II). Methods: The eukaryotic plasmids pVAX-GRA35, pVAX-GRA42, and pVAX-GRA43 were constructed, and formulated into two-genes or three-genes cocktail DNA vaccine. The indirect immunofluorescence assay (IFA) was used to analyze their expression and immunogenicity. Mice were immunized with a single-gene, two-genes or a multicomponent eukaryotic plasmid, intramuscularly. We assessed antibody levels, cytotoxic T cells (CTL) responses, cytokines, lymphocyte surface markers by using flow cytometry. Additionally, mouse survival and cyst numbers in the brain of mice challenged 1 to 2 months post vaccination were determined. Results: The specific humoral and cellular immune responses were elicited in mice immunized with single-gene, two-genes or three-genes cocktail DNA vaccine, as indicated by significant increases in serum antibody concentrations of total IgG, IgG2a /IgG1 ratio, cytokine levels (IFN-γ, IL-2, IL-12, IL-4 and IL-10), lymphocyte proliferation, lymphocyte populations (CD4+ and CD8+ T lymphocytes), CTL activities and survival as well as decreased brain cysts, in comparison with control mice. Moreover, Compared with pVAX-GRA35 + pVAX-GRA42, pVAX-GRA42 + pVAX-GRA43, or pVAX-GRA35 + pVAX-GRA43, multicomponent DNA vaccine with three-genes (pVAX-GRA35 + pVAX-GRA42 + pVAX-GRA43) induced the higher humoral and cellular immune responses, including serum antibody concentrations, cytokine levels, lymphocyte proliferation, lymphocyte populations, CTL activities and survival, resulting in prolonged survival time and reduced brain cyst loads. Furthermore, mice immunized with pVAX-GRA35 + pVAX-GRA42, pVAX-GRA42 + pVAX-GRA43, or pVAX-GRA35 + pVAX-GRA43 showed greater Th1 immune responses and protective efficacy than the single-gene-vaccinated groups.Conclusion: These results demonstrate that TgGRA35, TgGRA42 or TgGRA43 are vaccine candidates against T. gondii infection, and the three-genes DNA vaccine cocktail conferred the strongest protection against T. gondii infection.